Effect of ZnO-SiO2 nanoparticles on the morphology of nanocoating - Johari, Norhasnidawani; Hassan, Noor Azlina (The Mattingley Publishing Co., Inc., 2020)
The objective of this research is to investigate the interfacial compatibility of metal oxide nanoparticles and epoxy as the nanocoating. The sol is synthesized by the copolymerization of epoxy resin and hardener with the incorporation of metal oxide nanoparticles, which is Zinc Oxide (ZnO) and Silica (SiO2). Epoxy and hardener acted as a host while the metal oxide nanoparticles acted as guest components. Nanoparticles are uniformly distributed throughout the coating on the silicon wafer. Nanoparticles provide the resin or coating with a continuous, solid and protective network layer. SEM and FESEM images showed that the nanoparticles form a unique elastomeric structure within the coating. Nanoparticles improved the quality of the cured epoxy coating, reduced the porosity of the coating matrix, leading to the improved barrier performance of the epoxy coating.